Incidence of Domestic Violence Against Pregnant Females After the Great East Japan Earthquake in Miyagi Prefecture: The Japan Environment and Children's Study. (27th July 2016) - Sakurai, Kasumi; Nishigori, Hidekazu; Nishigori, Toshie; Mizuno, Satoshi; Obara, Taku; Iwama, Noriyuki; Watanabe, Zen; Ishikuro, Mami; Tatsuta, Nozomi; Nishijima, Ichiko; Sugawara, Junichi; Fujiwara, Ikuma; et al.
Abstract: Objective: This study aimed to clarify the correlation between the 2011 Great East Japan Earthquake and domestic violence (DV) against pregnant females after the disaster in Miyagi Prefecture, an area damaged by the earthquake and tsunami. Methods: We analyzed 7600 pregnant females from June to December 2011. The incidence of physical and mental DV and the proportions in the inland, north coastal, and south coastal areas of Miyagi Prefecture and nationwide were calculated, and a chi-square test was conducted for comparison. The risk factors for DV were estimated with multivariate logistic regression analyses on a prefecture-wide basis. Results: The incidence levels for physical DV were found to be 5.9% in the north coastal area, which was significantly higher than in the inland area (1.3%, P =0.0007) and nationwide (1.5%, P <0.0001). There were no significant differences in the incidence of mental DV between the 3 areas in Miyagi Prefecture (inland 15.2%, north coast 15.7%, and south coast 18.8%) or nationwide (13.8%). Experiencing disease or injury in someone close and changes in the family structure were significantly associated with mental DV in Miyagi Prefecture. Conclusion: Continuous monitoring and support for pregnant females may be necessary to address this issue in disaster-affected areas. ( Disaster Med Public Health Preparedness . 2017;11:216–226)